Is cholecystostomy tube insertion a real bridge for cholecystectomy in acute cholecystitis? A retrospective cohort study - Abdullah M Alotaibi (Saudi Journal for Health Sciences, 2019)
Background: Percutaneous cholecystostomy (PC) is an alternative treatment in high-risk acute cholecystitis (AC) patients. However, it is debatable whether PC should be considered as a definitive procedure or to be used as a temporizing measure before the definitive cholecystectomy. The aim of this study is to determine if PC is always a bridge for interval cholecystectomy in patients treated at tertiary care center in Saudi Arabia.Materials and Methods: This retrospective cohort study was conducted at a tertiary care center in Saudi Arabia for patients who underwent PC for AC during the period from January 2010 to January 2015. We evaluated the PC tube indications, complications, and outcomes (successful response).Results: A total of 63 patients were included in this study. Around half of the patients were male (54%) with a median age of 69 years. The median hospital length of stay was 17 days, in which 30% of the patients were admitted to the intensive care unit, with a hospital mortality of 25%. The successful response to PC was 79%, with 21% of patients undergoing cholecystectomy.Conclusion: PC is not always a bridge for interval cholecystectomy. However, more studies for patients in whom PC is selected as definite treatment are required.